PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA DAN PENGARUH IKUTANNYA TERHADAP KINERJA KEUANGAN - Sarjono, Putri Mandra (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to test the influence of corporate governance mechanism to the earningsmanagement, and its influence to the financial performance at the companies which are listed in Indonesia StockExchange. The research subjects in this research are manufacturing companies in basic industry and chemicalssector which are listed in Indonesia Stock Exchange since 2010 until 2012 and the samples are 39 companies andhave been selected by using purposive sampling. The test result shows that corporate governance mechanism hasno influence to the earnings management. The earnings management has influence to the financial performancewith the influence value of 0,166 indicates that the earnings management is done with the expectation toincrease the companyâs financial. Corporate governance mechanism either simultaneous or partial has influenceto the financial performance. The partial test result shows that institutional ownership and managerialownership have no influence to the financial performance with the siginificance level for institutional ownershipof 0,557 and for managerial ownership of 0,608. While the proportion of independent board of directors andaudit committee have influence to financial performance with figures for each effect of -0,231 and -0,432.Keywords: Corporate Governance, Earnings Management, Financial Performanace.